PMO-252 Efficacy of infliximab therapy in acute and sub-acute ulcerative colitis. (28th May 2012) - Harrison, E; Slater, J; Wood, L; Cooper, S C; de Silva, S
Abstract : Introduction: Ulcerative colitis (UC) has a chronic relapsing course. Infliximab is beneficial in severe disease, but conflicting data exists regarding the subsequent colectomy rates. We aimed to review outcomes post-infliximab usage in acute and sub-acute UC in our clinical practice. Methods: We conducted a retrospective review of all patients who had received a maximum of three doses of infliximab for acute or sub-acute exacerbations of UC between January 2010 and October 2011. Medical treatment (initial and subsequent) and colectomy rates were recorded for all patients. Results: 21 patients received infliximab during the study period. 12 patients were emergency admissions who had failed to respond to intravenous steroid therapy (acute group). Nine patients had failed to respond to maximum oral therapy, which included immunomodulators and oral prednisolone (sub-acute group). In the acute group, 42% (n=5) of patients had avoided a colectomy at a median follow-up of 467 days (IQR 370–612). The other 58% (n=7) proceeded to colectomy after a median of 69 days (IQR 30–136). Of the patients who proceeded to colectomy, 57% had been prescribed immunomodulator therapy prior to infliximab usage. However, all the patients who avoided colectomy were immunomodulator naive prior to infliximab. In the sub-acute group, only 33% (n=3) of patients required a colectomy after a median follow-up of 153 days (IQR 110–180). The remaining 67% (n=6) were well and off steroids after a median of 303 days (IQR 209–400). Conclusion: This review of patient outcomes shows the potential benefits of infliximab for treating both acute and sub-acute UC. After a maximum of three doses of infliximab, 42% of acute and 67% of sub-acute UC patients were able to avoid a colectomy. Our results are comparable to those of Oxford (1 to 7 doses of infliximab as needed) who reported that 43% of acute and 50% of sub-acute were able to avoid a colectomy. 1 Furthermore, our results confirm the greater potential benefit of infliximab in acute, immunomodulator naive patients. In addition, all sub-acute patients, who avoided colectomy, were well and off steroids at the end-of follow-up, compared to only 38% from the Oxford group, suggesting additional benefit from planned infliximab doses. 1 Competing interests: None declared. Reference: 1. Jakobovits SL, Jewell DP, Travis SPL. Infliximab for the treatment of ulcerative colitis: outcomes in Oxford from 2000 to 2006. Aliment Pharmacol Ther 2007;25 :1055–60.